VOLATILE COMPOSITION AND ANTIBACTERIAL ACTIVITY OF CEIBA INSIGNIS FLOWERS - AMJAD, M; INTISAR, A; SATTAR, T; HUSSAIN, T; BATOOL, N; AHMAD, S; MUTAHIR, Z; CHATTHA, MB (Biological and Clinical Sciences Research Journal, 2024)
This study reports the volatile oil composition and antibacterial activity of the flower of Ceiba insignis. Oil extraction was carried out by microwave-assisted distillation where a yield of 0.11% was obtained. A total of 17 compounds were successfully identified by gas chromatography mass spectrometry out of which the most abundant constituents were furfural (20.18%), heptadecan-2-one (13.81%), pentacosane (10.82%), methyl-5-furfural (8.27%), heptacosane (6.09%) and phytol (5.88%). The antibacterial potential of this oil was evaluated by using the agar disc diffusion technique against 4 different strains. The oil exhibited the highest activity against K. pneumoniae (12.7mm), followed by S. aureus (12mm), E. coli. (11mm) and P. aeruginosa (10.7mm).